Supramolecular peptide nanostructures: Self-assembly and biomedical applications - Zhen Du (Elsevier, 2022)
To mimic proteins, artificial designed self-assembling peptides (SAPs) that form diverse ordered nanostructures have been developed and served in biomedicine fields. In this review, we focus on four types of readily synthesized SAPs, including short aromatic peptides, peptide amphiphiles, amphipathic peptides, and surfactant-like peptides. Governed by multiple non-covalent interactions, sequence-coded and condition-altered self-organization of SAPs are presented, leading to the formation of versatile morphologies. The assembly of SAPs is an adaptable platform to incorporate with multiple bioactive motifs by chemical conjugation and physical encapsulation. These multifunctional SAPs-based nano-systems have demonstrated great potential to realize (i) combination therapies for synergetic anticancer effect, (ii) multimodal tumor imaging, (iii) antimicrobial materials that alleviate the drug-resistance problem, (iv) targeting and responsive hemostasis, and (v) active tissue regeneration. Future endeavor is encouraged to focus on the interactions between assemblies and cells, and the development of multi-component assemblies to facilitate the clinical translation of SAPs.